A Cross-sectional Study on Nomophobia among Undergraduate Medical Students in Chennai, India - Ganesh Shanmugasundaram Anusuya; Hanscie Dinah; Balaji Arumugam; Recharla Chenchu Karth; Radhakrishnan Annamalai; Ezhilvanan Mani (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Nomophobia is the fear of being away from mobile phone contact or in other words nomophobia is the irrational fear of being without mobile phone. Nomophobia is an emerging psychological public health problem. Aim: To determine the prevalence of nomophobia and pattern of mobile phone usage among medical students in Chennai. Materials and Methods: This cross-sectional study was done among 400 undergraduate medical students of Tagore Medical College and Hospital, Chennai, Tamil Nadu, India, studying from 1st year to 4th year, over a period of two months (July 2019 and August 2019). A structured questionnaire, developed by Yildirim C and Correia AP, was used to determine the prevalence of nomophobia among the study population. Stratified simple random sampling technique was used, where 100 students from each study year were selected. Descriptive statistics and chi-square test were done to compare the severity of nomophobia with various variables. Results: Out of 400 students, 50% (200) were males and 50% (200) were female students. Overall, 85% (340) used mobile internet. The top three reasons for using mobile internet were WhatsApp (95%), YouTube (81.3%) and Instagram (74.3%). The overall prevalence of nomophobia was 99% (396); 17.5% (70) showed severe nomophobia, 56.3% (225) moderate nomophobia, and 25.3% (101) had mild nomophobia. Severe nomophobia was associated with mobile usage >5 hours in a day (p-value=0.013). Conclusion: Health education and health awareness campaigns regarding nomophobia should be created among the undergraduate medical students.